A bibliometric analysis of inflammatory bowel disease and COVID-19 researches - Wang, Fangfei; Xie, Jinliang; Xiong, Huifang; Xie, Yong (Frontiers in Public Health, 2023)
Background: Patients with inflammatory bowel disease (IBD) often require immunosuppressive therapy and are hence susceptible to various opportunistic viral and bacterial infections. In this regard, many studies on IBD and coronavirus disease 2019 (COVID-19) have been conducted. However, no bibliometric analysis has been performed. This study provides a general overview of IBD and COVID-19. Methods: Publications about IBD and COVID-19 from 2020 to 2022 were retrieved from the Web of Science Core Collection (WoSCC) database. Bibliometric analysis was performed using VOSviewer, CiteSpace, and HistCite. Results: A total of 396 publications were retrieved and considered in this study. The maximum number of publications were from the United States, Italy, and England, and the contributions of these countries were significant. Kappelman ranked first in article citations. The Icahn School of Medicine at Mount Sinai and Inflammatory Bowel Diseases were the most prolific affiliation and journal, respectively. The most influential research topics were “management”, “impact”, “vaccination”, and “receptor”. The following keywords represented research frontiers: “depression”, “the quality of life of IBD patients”, “infliximab”, “COVID-19 vaccine”, and “second vaccination”. Conclusions: Over the past three years, most studies on IBD and COVID-19 have focused on clinical research. In particular, topics such as “depression”, “the quality of life of IBD patients”, “infliximab”, “COVID-19 vaccine”, and “second vaccination” were noted to have received much attention recently. Future research should focus on our understanding of the immune response to COVID-19 vaccination in biologically treated patients, the psychological impact of COVID-19, IBD management guidelines, and the long-term impact of COVID-19 in IBD patients. This study will provide researchers with a better understanding of research trends on IBD during COVID-19.